2014
DOI: 10.1038/modpathol.2013.138
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and clinico-pathologic analysis of metastatic uveal melanoma

Abstract: Uveal melanoma is the most common malignant tumor of the adult eye. Fifty percent of tumors will eventually metastasize, and there are no effective treatments for them. Recent studies of uveal melanoma have identified activating mutations in GNAQ and GNA11, loss-of-function mutations in the tumor suppressor gene BAP1, and recurrent mutations in codon 625 of SF3B1. Previous studies have reported the existence of a higher frequency of GNA11 than GNAQ mutations, frequent BAP1 loss, and rare SF3B1 mutations in met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
56
2
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 25 publications
5
56
2
6
Order By: Relevance
“…This is in contrast to previous finding that SF3B1 R625 mutations are rare in metastatic tumors and are associated with better prognosis [2, 4, 7]. Harbour et al did not detect any SF3B1 mutation in their five distant metastatic uveal melanoma [2], and Griewank et a l found one out of 26 metastatic uveal melanoma samples [7]. The difference might be due to sample bias, since there are more metastatic than primary tumors in our cohort.…”
Section: Discussioncontrasting
confidence: 98%
“…This is in contrast to previous finding that SF3B1 R625 mutations are rare in metastatic tumors and are associated with better prognosis [2, 4, 7]. Harbour et al did not detect any SF3B1 mutation in their five distant metastatic uveal melanoma [2], and Griewank et a l found one out of 26 metastatic uveal melanoma samples [7]. The difference might be due to sample bias, since there are more metastatic than primary tumors in our cohort.…”
Section: Discussioncontrasting
confidence: 98%
“…Another investigation found a mutation frequency of 45% (29/64) for BAP1 in unselected cases using exome and Sanger sequencing 8 . Whole-exome sequencing of metastatic uveal melanoma identified inactivating somatic mutations in BAP1 in 81-84% of metastatic tumors 10 , 16 . Ewens et al reported that 77% of uveal melanomas carrying BAP1 mutations developed metastasis 17 .…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of spindle cell histology is more frequent in younger patients and has decreased over time [10], probably as a consequence of increased age at diagnosis. Accordingly, metastatic UM shows prevalently epithelioid cells although a component of spindle-like cells is always present [126]. Other histopathological features commonly used for assessing the malignant potential of UM are the number of mitotic figures and the presence of extracellular matrix periodic acid–Schiff-positive closed loops.…”
Section: Clinical Features Of Uveal Melanomamentioning
confidence: 99%
“…Many studies report mutation frequencies that are summarized in Table 3 [27, 28, 30, 32, 35, 83, 126, 128, 130, 147, 148, 157172]. Initially, BRAF mutations had also been described for UM [173, 174] but these reports have not been confirmed.…”
Section: Genetics Of Uveal Melanomamentioning
confidence: 99%